Force monitoring tool to monitor mold cleanliness in a transfer molding machine - Ho, John Thiam Yong. (2010)
Mold cavity cleanliness has always been a major productivity issue in any type of molding processes because it affects the functionality, surface finish and/or quality of the end product, especially for transfer molding of electronic packages where too much ejection force due to sticky molds will damage the delicate and thin electronic package. The use of mold release agents in the molding compound and during the mold cleaning process only served to prolong the cleanliness of the mold cavity; it does not completely eliminate the issue of the sticky molding compound residue buildup in the mold cavities. Thus, periodic and time consuming manual cleaning of the mold cavities is required; causing significant downtime and productivity loss. The residue buildup is the main cause of excessive ejection forces on the molded part. This project attempted to measure and monitors the ejection forces experienced by an electronic package in a transfer molding machine after consecutive molding cycles. This was accomplished by designing and building a force measurement tool to indirectly measure and record the ejection force. The recorded data had been analyzed offline and the changes of the ejection force with deteriorating mold cleanliness had been observed.